2017
DOI: 10.1111/sdi.12574
|View full text |Cite
|
Sign up to set email alerts
|

Reuse and Biocompatibility of Hemodialysis Membranes: Clinically Relevant?

Abstract: The practice of reprocessing dialyzers for reuse, once predominant in the United States, has been steadily declining over the last 20 years. The professed roles of reuse in improving dialyzer membrane biocompatibility and lowering the risk of first-use syndrome have lost relevance with the advent of biocompatible dialyzer membranes and favorable sterilization techniques. The potential for cost-savings from reuse is also called into question by the easy availability of comparatively cheaper dialyzers and rising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…In low-to-middle-income countries, the practice of dialyzer reuse is common [ 67 , 68 ]. However, multiple dialyzer reuse may contribute to negative outcomes [ 69 ] such as infection risks, biochemical and immunologic reactions, improper sterilization, increased membrane permeability [ 49 ], and loss of performance leading to inadequate dialysis adequacy.…”
Section: Iatrogenic Factors Of Malnutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…In low-to-middle-income countries, the practice of dialyzer reuse is common [ 67 , 68 ]. However, multiple dialyzer reuse may contribute to negative outcomes [ 69 ] such as infection risks, biochemical and immunologic reactions, improper sterilization, increased membrane permeability [ 49 ], and loss of performance leading to inadequate dialysis adequacy.…”
Section: Iatrogenic Factors Of Malnutritionmentioning
confidence: 99%
“…However, multiple dialyzer reuse may contribute to negative outcomes [ 69 ] such as infection risks, biochemical and immunologic reactions, improper sterilization, increased membrane permeability [ 49 ], and loss of performance leading to inadequate dialysis adequacy. These issues are believed to arise from the reprocessing procedure involving sanitizing agents [ 67 , 70 ]. However, two studies have indicated that single, minimal (>6 times), or multiple dialyzer reuse carries no impact on dialysis adequacy, body weight, and serum albumin level [ 71 , 72 ].…”
Section: Iatrogenic Factors Of Malnutritionmentioning
confidence: 99%
“…15,16 In addition, although some studies show that the all-cause mortality in patients undergoing high flux dialysis may be lower compared to low flux hemodialysis, 15,17 this subject is still a matter of controversy. 18 The association of age and higher levels of bicarbonate had already been reported 3,18 and can be interpreted as a consequence of the lower acid generation in the dialysis interval due to the sarcopenia and reduced physical activity that can affect older hemodialysis patients. Although higher values for Kt/V 3,19 and duration of dialysis session 18 have been individually associated with higher levels of serum bicarbonate, we could not find studies addressing the role of the standard Kt/V in this regard.…”
Section: Discussionmentioning
confidence: 85%
“…The low quality of the evidence in the available studies, acknowledged in the only systematic review we were able to retrieve, and the heterogeneity of the reuse modalities suggest that the time may be ripe for re-thinking this practice in the different context of ecological sustainability. In this regard, future studies should balance the advantages in reducing plastic waste with the need for using potentially toxic chemicals for membrane sterilization [94][95][96][97].…”
Section: Waste Management In Dialysismentioning
confidence: 99%